Korelasi Kegiatan Ekstrakurikuler Sanggar Al-Quran dengan Hasil Belajar Al-Quran Hadits di MAN 4 Pasaman Barat - Nur Alim; Mahyudin Ritonga; Mafardi Mafardi (UMSU, 2020)
This article aims to determine the correlation of the extracurricular activities of the al-Quran workshop with the results of learning the Qur'an hadith in MAN 4 Pasaman Barat, regency of West Pasaman. These types of research are quantitative descriptive and field research. Method of research that authors use the documentation of the value of subjects Qur'anic hadith. Secondary data source is, the value of the workshop obtained from the results of extracurricular activities of the Qur'an in MAN 4 Pasaman Barat, namely data obtained from the poll is poured in SPSS. The results showed that in MAN 4 Pasaman Barat, regency of West Pasaman, programmatic in the form of extracurricular activities of the Qur'anic religious workshop consisting of Tilawatil Qur'an, Fahmil Qur'an, Syahril Qur'an, Khottil Qur'an, Qur'anic poeisation, Nasheed. Results of analysis of the correlation between activities of the workshop al-Quran with the results of learning al-Quran Hadith is concluded that the extracurricular al-Quran workshop has a close relation with the results of learning al-Quran Hadith, the implications of this research is the need to increase extracurricular instensities in support of the intrurricular success.